Effect Of Bolt Diameter On The Bearing Capacities Of Bolted Fibre Cemboard: A Numerical Modelling Using FEM - Rahman, Syahir; Mohd Jaini, Zainorizuan (Recent Trends in Civil Engineering and Built Environment, 2021)
Fibre cemboard is one of the most important meterials used in the construction of buildings. The application of fibre cemboard has led to the prefabricated and build-up system known as bolted-fibre cemboard to be used as floor system. However, the knowledge about bearing capacity of bolted-fibre cemboard is not readily available. Therefore, this study aim to numerically investigate the bearing capacity of bolted-fibre cemboard in term of bearing resistance, slip-displacement and failure mode. The numerical modelling of two-layer bolted-fibre cemboard with size 210mm length x 210mm width will be conducted using the Finite Element Method (FEM). The diameter of bolted-fibre cemboard is caries from 10mm up to 24mm. The mesh that will be used in the numerical modelling is based on four-noded tetrahedral element. Plasticity material model with hardening properties will be define in the fibre cemboard and steel bolt, respectively as the constitutive laws. The loading that will be applied is based on push out test in term of stroke-time history. Furthermore, the relation of diamerter bolted-fibre cemboard with ultimate load and maximum displacement was also establish. It was found that the larger steel bolt diameter is used, the bearing capacity increased steadily compared to deformation that as the steel bolt diameter is increased, the slip-displacement decreases gradually. Overall, the final result of this study shows that bolted-fibre cemboard has a good potential as a structural member due to exelent serviceability.